When nanocellulose meets diffraction grating: freestanding photonic paper with programmable optical coupling. Issue 2 (10th October 2019) - Chu, Guang; Qu, Dan; Camposeo, Andrea; Pisignano, Dario; Zussman, Eyal
Abstract : Bio-inspired chiral nematic cellulose films with periodic surface grating structures exhibit optically programmable photonic–photonic coupling. Abstract : Photonic crystals based on plasmonic or dielectric periodic structures have attracted considerable interest owing to their capabilities to control light–matter interactions with tailored precision. By using a nanocellulose derived chiral liquid crystal as a building block, here we demonstrate a bio-inspired dual photonic structure that contains the combination of microscopic periodic 1D surface grating and nanoscopic helical organization, giving rise to programmable colour mixing and polarization rotation. We show that a variation in the photonic band-gap in the bulk matrix leads to simultaneous control over the reflection and diffraction of light with controllable iridescence.